YY1 expression predicts favourable outcome in follicular lymphoma. Issue 2 (25th November 2010) - Naidoo, Khimara; Clay, Vanessa; Hoyland, Judith A; Swindell, Ric; Linton, Kim; Illidge, Timothy; Radford, John A; Byers, Richard J
Abstract : Aims: Follicular lymphoma is the second most common type of non-Hodgkin's lymphoma worldwide. The majority of patients diagnosed as having follicular lymphoma have an indolent form of the disease, but a subset of patients have aggressive disease with a shorter survival interval. Optimal treatment stratification requires a distinction between these two groups, though there are presently few prognostic biomarkers available. The transcription factor YY1 has been shown to play an important role in cancer biology. The authors have previously reported a correlation of Yin Yang 1 (YY1) mRNA levels with survival in FL. This study aimed to validate these findings at the protein level. Methods: Quantification of YY1 protein was carried out on 26 FL biopsy samples using quantum dot labelled immunohistochemistry. Ki-67 percentage, grade, YY1 protein levels and T cell and macrophage markers were used in a multivariable analysis for survival in 26 cases of FL. Results: Expression levels of YY1 protein were significantly increased in patients alive in comparison with those dead after follow-up (p≤0.025). Kaplan–Meier analysis showed association of higher expression levels of YY1 with longer survival (p≤0.01) (hazard ratio 3.33, 95% CI 1.26 to 8.85). The multivariable analysis identified YY1 protein level as the strongest predictor of outcome (p≤0.018), with none of the other markers being significantly associated with outcome. Conclusion: These results support the prognostic utility of YY1 in FL, indicating potential as a clinical biomarker.